Four women at the end of the world - Rebe Taylor (2022)
Dolly Pentreath of Cornwall (1692-1777); Shanawdithit of Newfoundland (c.1801-1829); Trukanini of lutruwita/Tasmania (c.1812-1876); and, Cristina Calderón of Tierra del Fuego (1928-2022), have all, famously and wrongfully, been named by imperialist Europeans as being the ‘last’ speaker of their language or the last member of their ‘tribe’ or ‘race’. In fact, all these women have been survived by communities who challenge the idea of their groups’ ‘extinction’. How and why did this contradiction occur? Through modern history, European imperialists have imposed the moniker of ‘last’ upon Indigenous individuals as a way to both mourn and celebrate their own expansionist powers. Most of these ‘last’ peoples have been women living at the edges of continents. The geographical and gendered nature of extinction discourse has, however, been little examined by historians. Indeed, there are no histories of imperial extinction discourse that extend beyond the ‘doomed race’ theories of the long nineteenth century, or that include a counter discourse of Indigenous survival and resurgence. This presentation considers how an exploration of the lives of the abovenamed four women might address this historiographical gap.